Terapija z ogledalom za zgornji ud pri pacientu po možganski kapi - poročilo o primeru - Pišek, Irena (Rehabilitacija (Ljubljana), 2012)
Background: Mirror therapy is a recent method that has already been used in patients after stroke. Mirror therapy facilitates the recovery of paretic limb movement by using the nonparetic limb movement to treat the paretic limb. The purpose of our study was to investigate the suitability of mirror therapy for upper extremity in a patient after stroke in the home environment. The effects of mirror therapy on passive range of movement, hand and pinch grip strenght, sensibility, spasticity, dexterity and motor functions of the paretic upper limb were assessed. Methods: A 38-year old man, 11 months after stroke, with right hand dominance was assessed. Mirror therapy continued for four weeks (24 days), six days per week. Goniometry of the wrist joint, dynamometry using pinch Jamar dynamometer, assessment of light touch sensitivity threshold using Semmes Weinstein monofilaments, static and dynamic two point discrimination using Disk-Criminator, assessment of proprioception and kinesthesia, modified Ashworth scale, nine hole peg test and partial modified assessment scale for stroke patients were performed before and after the period of mirror therapy. Results: After mirror therapy, passive range of motion of the wrist joint for the dorsiflexion improved by 10°, grip strength improved by 5.7 kp, and pinch grip improvement (key: by 1.6kp; palmar: by 9.6 kp; tip pinch: by 1.5 kp) was also observed. Performance time of the nine hole peg test decreased by 28 s and the partial motor assessment scale score improved by three grades. Conclusion: Mirror therapy was an appropriate therapeutic method for facilitation of the paretic upper limb movement recovery in the studied case. The use of mirror therapy in the home environment without or with minimum supervision remains an open issue.
Keywords: mirror therapy; možganska kap; Paresis; pareza; rehabilitacija; Stroke; terapija z ogledalom; Upper Extremity; vocational rehabilitation; zgornji ud